Level of patient satisfaction after subcutaneous mastectomy in gynecomastia (Panacea Journal of Medical Sciences, 2022)
Objectives: The objective of our study was to assess satisfaction in patients undergoing subcutaneous mastectomy for gynecomastia.Materials and Methods: A retrospective analysis of patients undergoing subcutaneous mastectomy without additional liposuction, from July 2016 to February 2020 in a tertiary care centre in south India, was conducted. They were approached over phone with a questionnaire; their response was recorded and mean value of each variable (total 10 variables) was tabulated against grade of gynecomastia and age interval. The sum of the mean values was taken as patient satisfaction score (PSS) and was grouped into very good satisfaction (15-20), good satisfaction (10-15), average satisfaction (5-10) and poor satisfaction (0-5); for each grade and in each age interval.Results: The patients with grade 1 and 2A gynecomastia showed very good satisfaction after Subcutaneous Mastectomy, with average score of 18.71 and 17.28 respectively; where as those with grade 2B showed good satisfaction, with average score 13.Conclusions: Very Good patient satisfaction and surgical outcome can be obtained after subcutaneous mastectomy in grade 1 and grade 2A gynecomastia which improved body image and thereby quality of life.